Severe Conjunctivitis Associated with Chlamydia felis Infection in a Free-ranging Eurasian Lynx ( Lynx lynx). - Marti, Iris Andrea; Pisano, Simone; Wehrle, Martin; Meli, Marina L; Hofmann-Lehmann, Regina; Ryser, Marie Pierre (Journal of Wildlife Diseases, 2019)
A free-ranging adult Eurasian lynx ( Lynx lynx) captured in Switzerland presented with a severe purulent unilateral conjunctivitis. Chlamydia felis was detected in conjunctival swabs by qPCR. Systemic treatment with oxytetracycline and ketoprofen led to complete recovery. Infection with C. felis has not been previously reported in Eurasian lynx.